The Effect of Boycott on Long-Term Stock Performance - Gilang Rahmat Hastanto; Dony Abdul Chalid (UNIVED Press, 2025)
Previous studies regarding the impact of boycott have only been studied for a short-term period. This study uses the calendar-time portfolio method to see how the impact of the boycott on the long-term stock performance of companies whose products are the targets of the boycott. We collected stock prices data from affected company for one year after MUI released Fatwa number 83 of 2023 concerning the Law on Support for the Palestinian Struggle. The data processed with calendar-time portfolio method to find abnormal return. The result shows that the boycott on products that suspected of being affiliated with Israel resulted in a negative daily abnormal return of -0.26% and was statistically significant. Based on literature review, there is no previous study that addressed boycott as a long-term event that affecting stock prices. The originality of this study is to consider long-term effect of boycott on stock prices.